Connectedness to Campus and Likelihood of Help-Seeking for Suicidality among College Women. Issue 3 (3rd July 2017) - Samuolis, Jessica; Griffin, Kenneth; Mason, Mary Jo; Dekraker, Nancy
ABSTRACT: The goal of the present study was to examine the link between connectedness to campus and the likelihood of help-seeking from a mental health professional/school counselor for thoughts of suicide among college women. An online survey was administered to college students to assess perceived likelihood of seeking help, feelings of connectedness to campus, sense of togetherness with peers, and presence of a supportive group of friends on campus. Findings indicated that feeling connected to campus was positively associated with perceived likelihood of help-seeking for suicidal ideation. Furthermore, this association was stronger among participants reporting either a sense of togetherness with peers or a supportive group of friends. Efforts to increase students' sense of connection to the larger campus community and build peer relationships may promote help-seeking for suicidal ideation among college women.